2016
DOI: 10.21082/bullittro.v26n2.2015.109-116
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTIVITY OF CITRONELLA AND CLOVE OILS AGAINTS CABBAGE CATERPILLAR Crocidolomia pavonana

Abstract: Crocidolomia pavonana is a major pest on cabbage crops. The use of chemical pesticides in pest control of C. pavonana is not the proper solution due to the fact that the chemical pesticides are not environmentally friendly, kill natural enemies and have negative impacts on human health. The aim of this study is to determine the effectiveness of the botanical pesticide consisting of citronella and eugenol oils to control C. pavonana. The treatment was conducted by using two methods based on the control target, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Thus far, there has not been any growth in the number of attack cases based on the data from BTNK [50], where 32 cases of Komodo attacks from 1974 to 2017 were recorded, with the highest frequency occurring in Loh Buaya (Rinca Island) (Table 3). This is inline with Rismayani [51] who found that Komodo attacks on humans occurred more on Rinca Island than in Komodo Village.…”
Section: Perceptions Of the Human-komodo Interactionssupporting
confidence: 83%
“…Thus far, there has not been any growth in the number of attack cases based on the data from BTNK [50], where 32 cases of Komodo attacks from 1974 to 2017 were recorded, with the highest frequency occurring in Loh Buaya (Rinca Island) (Table 3). This is inline with Rismayani [51] who found that Komodo attacks on humans occurred more on Rinca Island than in Komodo Village.…”
Section: Perceptions Of the Human-komodo Interactionssupporting
confidence: 83%
“…The previous study using single CTO and CLO (at a concentration of 2.5 -5.0 ml l -1 ) showed a decrease in D. piperis compared to control and was not significantly different from synthetic insecticides [7]. Another report [13] stating that CTO at a concentration of 2 ml l -1 was more effective than CLO to control Crocidolomia pavonana on cabbage with a mortalities rate of 76-88%.…”
Section: Field Testingmentioning
confidence: 96%
“…The addition of CTO and CLO can reduce the use of Cyp insecticides. CTO and CLO, which contain more than one active ingredient that affects insects combined CTO with fast-acting Cyp, can increase the efficiency of insecticide performance, reduce dependence on one insecticide ingredient, and slow down the occurrence of insect resistance [13].…”
Section: Table 2 Population Average Of D Piperis Before (B) and After (A) Pesticides Treatmentsmentioning
confidence: 99%
“…Essential oils from aromatic and medicinal plants contained various natural substances used for insect management as botanical pesticides. Botanical pesticides can control the major pests of crops due to utilizing the secondary plant compounds as the active ingredient [8]. Essential oils contain volatile compounds which are known and used as bioactive agents [9].…”
Section: Introductionmentioning
confidence: 99%